Our Definition of Propeller Flaps and Their Classification - Pignatti, Marco; Ogawa, Rei; Mateev, Musa; Georgescu, Alexandru V.; Balakrishnan, Govindasamy; Ono, Shimpei; Cubison, Tania; Pinto, Valentina; D'Arpa, Salvatore; Koshima, Isao; Hyakusoku, Hiko; Hallock, Geoffrey G. (Seminars in Plastic Surgery, 2020)
The term propeller flap was introduced for the first time by Hyakusoku to define an island flap, based on a subcutaneous pedicle hub, that was rotated 90 degrees to correct scar contractures due to burns. With the popularization of perforator flaps, the propeller movement was applied for the first time to a skin island vascularized only by an isolated perforator, and the terms propeller and perforator flap were used together. Thereafter, the surgical technique of propeller flaps evolved and new applications developed. With the “Tokyo consensus,” we proposed a definition and a classification schema for propeller flaps. A propeller flap was defined as an “island flap that reaches the recipient site through an axial rotation.” The classification included the SPP (SPP) flap, the perforator pedicled propeller (PPP) flap, and the supercharged PPP (SCP) flap. A recent update added a new category, the axial pedicled propeller (APP) flap. Here we propose our updated and comprehensive classification of propeller flaps, taking into account the previous classification and subsequent publications. Based on their vascular pedicle, we consider the following five types of propellers: (1) SPP flap, 2.PPP flap, its subtype (2a) SCP flap, (3) APP flap, (4) muscle propeller flap, and (5) chimeric propeller flap. The variables that can be taken into account in the classification are as follows: type of nourishing pedicle, degrees of skin island rotation, position of the nourishing pedicle, artery of origin of the pedicle, and flap shape.
Keywords: propeller flap; definition; classification; update